Python machine learning by example : build intelligent systems using Python, TensorFlow 2, PyTorch, and scikit-learn - Liu, Yuxi (Hayden) (Packt Pub, 2020)
Equipped with the latest updates, this third edition of Python Machine Learning By Example provides a comprehensive course for ML enthusiasts to strengthen their command of ML concepts, techniques, and algorithms.